Roles of endogenous retroviral elements in the establishment and maintenance of imprinted gene expression - Fang, Sherry; Chang, Kai-Wei; Lefebvre, Louis (Frontiers in Cell and Developmental Biology, 2024)
DNA methylation (DNAme) has long been recognized as a host defense mechanism, both in the restriction modification systems of prokaryotes as well as in the transcriptional silencing of repetitive elements in mammals. When DNAme was shown to be implicated as a key epigenetic mechanism in the regulation of imprinted genes in mammals, a parallel with host defense mechanisms was drawn, suggesting perhaps a common evolutionary origin. Here we review recent work related to this hypothesis on two different aspects of the developmental imprinting cycle in mammals that has revealed unexpected roles for long terminal repeat (LTR) retroelements in imprinting, both canonical and noncanonical. These two different forms of genomic imprinting depend on different epigenetic marks inherited from the mature gametes, DNAme and histone H3 lysine 27 trimethylation (H3K27me3), respectively. DNAme establishment in the maternal germline is guided by transcription during oocyte growth. Specific families of LTRs, evading silencing mechanisms, have been implicated in this process for specific imprinted genes. In noncanonical imprinting, maternally inherited histone marks play transient roles in transcriptional silencing during preimplantation development. These marks are ultimately translated into DNAme, notably over LTR elements, for the maintenance of silencing of the maternal alleles in the extraembryonic trophoblast lineage. Therefore, LTR retroelements play important roles in both establishment and maintenance of different epigenetic pathways leading to imprinted expression during development. Because such elements are mobile and highly polymorphic among different species, they can be coopted for the evolution of new speciesspecific imprinted genes.